Bilateral De Quervain Syndrome after Aromatase Inhibitor Administration: A Case Report and Review of the Literature - Konstantinos Papadimitriou; Panteleimon Kountourakis; Emmanouil Morakis; Vassilios Vassiliou; Vasileios Barbounis; Alexandros Ardavanis (Case Reports in Medicine)
Aromatase inhibitors are widely used as one of the main treatment options of both early and advanced hormone receptor-positive breast cancer in postmenopausal women. Unfortunately, musculoskeletal symptoms are often presented in patients treated with aromatase inhibitors (AIs), and, although the pathogenesis is unknown, postulated mechanisms have been described. Herein, to our knowledge, we present the first report of bilateral De Quervain syndrome related with AIs therapy with a review of the relevant literature.